Delayed postpartum haemorrhage secondary to a ruptured uterine artery pseudo-aneurysm, successfully treated by transarterial embolisation. (1st December 2011) - Moatti, Zoe; Nisner, Tamar; Saini, Ashish; Karoshi, Mahantesh
Abstract : A 29-year-old woman (gravida 1, para 1) had an uneventful first pregnancy and a delivery by emergency caesarean section at term. The caesarean section was complicated by a massive obstetric haemorrhage of 5000 ml. After closure, an immediate re-laparotomy was indicated due to heavy vaginal bleeding. The site of bleeding was identified as an extension of the uterine incision, and was sutured. She was stabilised by transfusion of blood and blood products in the intensive therapy unit, and discharged 5 days later. The patient was re-admitted 6 weeks later with brisk, painless vaginal bleeding, passing large clots from a well-contracted uterus. Her haemoglobin decreased from 11.8 to 7.8 g/dl overnight. In view of her history, an urgent CT angiogram was performed, which revealed the presence of a pseudo-aneurysm arising from the left uterine artery. This was successfully occluded by transarterial embolisation, obviating the need for further surgical exploration.